1 | 1 | 1 | 1 | 1 | 1 | 1 | 1 | ||||||||
+ | +...+ | =1− | + | − | +...+ | − | dla n ∈ N. | ||||||||
n+1 | n+2 | 2n | 2 | 3 | 4 | 2n−1 | 2n |
1 | 1 | 1 | ||||
L(n)= | + | +...+ | ||||
n+1 | n+2 | 2n |
1 | 1 | 1 | 1 | 1 | ||||||
P(n)=1− | + | − | +...+ | − | ||||||
2 | 3 | 4 | 2n−1 | 2n |
1 | ||
L(1)= | ||
2 |
1 | ||
P(1)=1− | ||
2 |
1 | 1 | 1 | ||||
L(n+1)= | + | +...+ | = | |||
(n+1)+1 | (n+1)+2 | 2(n+1) |
1 | 1 | 1 | ||||
= | + | +...+ | = | |||
n+2 | n+3 | 2n+2 |
1 | 1 | 1 | 1 | 1 | 1 | 1 | ||||||||
=− | + | + | + | +...+ | + | + | = | |||||||
n+1 | n+1 | n+2 | n+3 | 2n | 2n+1 | 2n+2 |
1 | 1 | 1 | ||||
=− | +L(n)+ | + | = | |||
n+1 | 2n+1 | 2n+2 |
1 | 1 | 2 | ||||
=L(n)+ | + | − | = | |||
2n+1 | 2n+2 | 2n+2 |
1 | 1 | |||
=L(n)+ | − | = // z założenia indukcyjnego L(n)=P(n) | ||
2n+1 | 2n+2 |
1 | 1 | |||
=P(n)+ | − | = | ||
2n+1 | 2n+2 |
1 | 1 | 1 | 1 | 1 | 1 | 1 | ||||||||
=1− | + | − | +...+ | − | + | − | = | |||||||
2 | 3 | 4 | 2n−1 | 2n | 2n+1 | 2n+2 |
1 | 1 | 1 | 1 | 1 | 1 | 1 | ||||||||
=1− | + | − | +...+ | − | + | − | = | |||||||
2 | 3 | 4 | 2(n+1)−3 | 2(n+1)−2 | 2(n+1)−1 | 2(n+1) |